EVALUATION OF CLINICAL OUTCOMES OF AUTOLOGOUS PLATELET-RICH PLASMA THERAPY FOR SIMPLE SHOULDER PERIARTHRITIS AT THONGNHAT HOSPITAL - Thành Toàn, Võ; Phi Trình, Nguyễn; Trọng Sỹ, Nguyễn (Journal of Health and Aging, 2026)
Autologous Platelet-Rich Plasma (PRP) is an increasingly popular biological therapy in sports medicine and rehabilitation, particularly for periarticular soft tissue pathologies of the shoulder. To evaluate the clinical efficacy of autologous PRP in treating simple shoulder periarthritis over a 4-month follow-up period and to analyze factors associated with treatment outcomes. Methods: A longitudinal clinical intervention study was conducted on 30 patients diagnosed with simple shoulder periarthritis. After 4 months, the mean Visual Analogue Scale (VAS) score significantly decreased from 5.6 to 2.6, accompanied by improvements in ultrasonographic findings. Greater pain reduction was observed in younger patients. Adverse effects were primarily limited to mild, self-limiting injection-site pain resolving within 3 days. Autologous PRP is a safe and effective treatment for shoulder periarthritis, especially in younger populations.